2012
DOI: 10.1080/00224545.2011.637997
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes Toward Cosmetic Surgery Patients: The Role of Culture and Social Contact

Abstract: Cosmetic surgery is increasingly popular globally, but how cosmetic surgery patients are socially evaluated is largely unknown. The present research documents attitudes toward these patients in multiple cultures (Hong Kong, Japan, and the United States). Across these cultures, attitudes toward cosmetic surgery patients were predominantly negative: Participants ascribed more negative attributes to cosmetic surgery patients and found cosmetic surgery not acceptable. Also, participants in Hong Kong and Japan were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0
5

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 28 publications
1
32
0
5
Order By: Relevance
“…Some as Chinese population found that body should not be intact as it is a guarantee from parents. [20] and people like normal things. [24] Ton Tam et al, in a study conducted in Hong Kong [20] (2012) found that participants were not even welling to marry women have had cosmetic surgery.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Some as Chinese population found that body should not be intact as it is a guarantee from parents. [20] and people like normal things. [24] Ton Tam et al, in a study conducted in Hong Kong [20] (2012) found that participants were not even welling to marry women have had cosmetic surgery.…”
Section: Discussionmentioning
confidence: 99%
“…[20] and people like normal things. [24] Ton Tam et al, in a study conducted in Hong Kong [20] (2012) found that participants were not even welling to marry women have had cosmetic surgery. On the other hand, this research is inconsistent with Al Doheyan and colleagues (2016) [16] who mentioned that female medical students attitude towards cosmetic surgery at Al Riyadh is reasonable and most of the students agreed that cosmetic surgery is common in general.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cosmetic surgery is increasingly popular, globally (8). In contemporary society, the media are largely responsible for providing universal Yardsticks (9).…”
Section: Introductionmentioning
confidence: 99%
“…Os autores identificaram que japoneses e chineses (nesse caso, de Hong Kong) sentem-se menos à vontade em falar sobre o tema e avaliam que as cirurgias estéticas são negativas, já que são formas de alterar a naturalidade do corpo. Ao contrário dos americanos, que possuem melhores atitudes em relação às cirurgias plásticas e sentem mais à vontade para falar sobre o assunto (TAM et al, 2012).…”
Section: Consumo E Cirurgias Plásticas Estéticasunclassified